2021
DOI: 10.1371/journal.pone.0252906
|View full text |Cite
|
Sign up to set email alerts
|

A network pharmacology approach to determine the underlying mechanisms of action of Yishen Tongluo formula for the treatment of oligoasthenozoospermia

Abstract: Oligoasthenozoospermia is a complex disease caused by a variety of factors, and its incidence is increasing yearly worldwide. Yishen Tongluo formula (YSTLF), created by Professor Sun Zixue, has been used to treat oligoasthenozoospermia in clinical practice for several decades with a good therapeutic effect. However, the chemical and pharmacological profiles of YSTLF remain unclear and need to be elucidated. In this study, a network pharmacology approach was applied to explore the potential mechanisms of YSTLF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…All ingredients about ZSS were first collected as candidates with the Chinese name “Suanzaoren” as the search term. Afterwards, we introduced these limiting parameters of oral bioavailability (OB) and drug-likeness (DL) according to the classical active ingredient screening rules [ 10 ], in which OB refers to the percentage of unmodified drugs that enter the circulatory system after oral administration and can effectively represent the availability of drugs, and OB ≥ 30% of compounds is considered as one of the screening rules for active ingredients [ 11 ]. While DL refers to the similarity of compounds to clinically used drugs, the greater DL value represents the possibility of compounds becoming drugs, and molecules with DL ≥ 0.18 are carefully thought about to have better pharmacological effects and are also one of the most commonly used active ingredient screening rules [ 12 ], so we started obeying this rule.…”
Section: Methodsmentioning
confidence: 99%
“…All ingredients about ZSS were first collected as candidates with the Chinese name “Suanzaoren” as the search term. Afterwards, we introduced these limiting parameters of oral bioavailability (OB) and drug-likeness (DL) according to the classical active ingredient screening rules [ 10 ], in which OB refers to the percentage of unmodified drugs that enter the circulatory system after oral administration and can effectively represent the availability of drugs, and OB ≥ 30% of compounds is considered as one of the screening rules for active ingredients [ 11 ]. While DL refers to the similarity of compounds to clinically used drugs, the greater DL value represents the possibility of compounds becoming drugs, and molecules with DL ≥ 0.18 are carefully thought about to have better pharmacological effects and are also one of the most commonly used active ingredient screening rules [ 12 ], so we started obeying this rule.…”
Section: Methodsmentioning
confidence: 99%
“…Its complex figures are depicted in Figure 8. β-Amyrone 612782 −16.1 (1) Clofibrate 2796 −6.4 (2) Gemfibrozil 3463 −6.3 (3) Ciprofibrate 2763 −5.4 (4) Bezafibrate 39042 −5.8 (5) Fenofibrate 3339 −5.4 β-Stigmasterol 6432745 −10.8 (6) Cardarine 9803963 −8.5 β-Amyrone 612782 −14.0 (7) Pioglitazone 4829 −7.7 (8) Rosiglitazone 77999 −7.4 (9) Lobeglitazone 9826451 −7.3 β-Amyrone 612782 −21.5 β-Amyrone 612782 −13.2 β-Amyrone 612782 −15.4 (10) GW3965 447905 −11.9 (11) T0901317 447912 −8.2 Neotocopherol 86052 −7.5 (12) AT13148 24905401 −6.9 (13) Afuresertib 46843057 −6.9 (14) Alliin 87310 −4.8 Xanthosine 64959 −7.4 (15) APX-115 free base 51036475 −7.2 (16) Resatorvid 11703255 −7.1 (17) Myrislignan 21636106 −7.1 (18) Muscone 10947 −6.7 (19) 2 ,5 -Dihydroxyacetophenone 10279 −6.5 (20) α-Cyperone −6.3 (21) Veratric acid 7121 −6.1 (22) Triolein −5.5 (23) Methylthiouracil 667493 −5.4 (24) Falcarindiol −5.2 Ethyl palmitate 12366 −6.4 (25) BAW2881 16004702 −7.6 Ethyl palmitate 12366 −6.4 (26) Midostaurin −11.0 Sitostenone −8.5 (27) Suramin 5361 −15.4 β-Amyrone 612782 −14.4 (28)…”
Section: The Construction Of a Signaling Pathway-target Protein-bioactive (Stb) Networkmentioning
confidence: 99%
“…Thus, the studies on drug-like compounds and promising mechanism(s) of CS against obesity should be strengthened to provide pharmacological evidence to support its therapeutic application in alleviating obesity. Network pharmacology is a significant methodology to elucidate multiple components such as signaling pathways, targets, and compounds [24]. Network pharmacology is a key to decipher multiple targets of herbal bioactive compounds [25].…”
Section: Introductionmentioning
confidence: 99%
“…Yishen Tongluo formula (YSTL) is composed of Semen Cuscutae (Tu‐Si‐Zi; TSZ), Herba Epimedii (Yin‐Yang‐Huo; YYH), Radix Rehmanniae Preparata (Shu‐Di‐Huang; SDH), Radix Astragali (Huang‐Qi; HQ), Salvia Miltiorrhiza (Dan‐Shen; DS), Leech (Shui‐Zhi; SZ), and Radix Cyathulae (Chuan‐Niu‐Xi; CNX). YSTL was created by Professor Sun Zixue and has been used to treat oligoasthenozoospermia in clinical practice for several decades with a good therapeutic effect (Chen et al, 2020, 2021; Zhang et al, 2020). Moreover, in our previous studies, we found that YSTL also reduced DFI (Chen et al, 2020) and prevented abnormal methylation of sperm DNA (Sun et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%